2023
DOI: 10.3389/fpsyt.2023.1178529
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability, and clinical and neural effects of single-dose psilocybin in obsessive–compulsive disorder: protocol for a randomized, double-blind, placebo-controlled, non-crossover trial

Abstract: BackgroundPsilocybin may help treat obsessive–compulsive disorder (OCD). To date, only one open-label study of psilocybin for OCD exists, necessitating further investigation with a randomized controlled design. The neural correlates of psilocybin’s effects on OCD have also not been studied.ObjectivesThis first-of-its-kind trial aims to evaluate the feasibility, safety, and tolerability of psilocybin in the treatment of OCD, provide preliminary evidence on the effects of psilocybin on OCD symptoms, and elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Participants will be randomized to receive treatment either immediately or at a later time (i.e., delayed treatment after a 7-week waitlist phase) (see Figure 1 ). As with prior research ( 39 , 56 , 57 ), participants will receive non-directive psychological support during each dosing session, during the two preparatory sessions in the week prior to the first dosing week, as well as during the two integration sessions in the same week following each dosing (i.e., 1 day and 4 days post-dosing). All preparatory and integration sessions last for up to 2 h each.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants will be randomized to receive treatment either immediately or at a later time (i.e., delayed treatment after a 7-week waitlist phase) (see Figure 1 ). As with prior research ( 39 , 56 , 57 ), participants will receive non-directive psychological support during each dosing session, during the two preparatory sessions in the week prior to the first dosing week, as well as during the two integration sessions in the same week following each dosing (i.e., 1 day and 4 days post-dosing). All preparatory and integration sessions last for up to 2 h each.…”
Section: Methodsmentioning
confidence: 99%
“…In response, in 2018, our group launched a randomized, double-blind, active placebo-controlled trial examining the feasibility, tolerability, safety, and clinical effects of a single moderate dose (0.25 mg/kg) of psilocybin paired with unstructured, non-directive psychological support in participants with treatment-refractory OCD ( 39 ). While this trial is still ongoing, early observations with a subsample of completers indicated clinically significant response on the Y-BOCS (i.e., < 35% reduction) at 48 h post-dosing for participants who received psilocybin ( 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…Also resting state neuroimaging data will be stored both at baseline and primary endpoint. It is expected that psilocybin might lead to a rapid and substantial reduction in OCD symptoms, hence it would be able to treat refractory OCD [36]. According to clinicaltrial.gov (last update mid-July 2023) the trial is still in the recruiting phase.…”
Section: Possibilities Of Using Psilocybin and Its Effectiveness In T...mentioning
confidence: 99%
“…O tratamento tradicionalmente indicado ao TOC baseia-se em terapia medicamentosa em conjunto com psicoterapia cognitivo-comportamental (TCC) sendo realizada a prevenção de exposição à resposta (PER). Dentre a classe dos medicamentos de primeira linha estão os inibidores seletivos da recaptação da serotonina (ISRSs), e embora os ISRS tenham se mostrado eficazes em ensaios clínicos randomizados controlados por placebo, até 60% dos pacientes não respondem e muitos pacientes com TOC classificados como respondedores em estudos de ISRS e TCC/PER permanecem sintomáticos e com restrições em suas vidas, sobretudo na realização das atividades de vida diária, com recidiva após a interrupção ou conclusão da TCC (Ching, et al;. Novos horizontes no tratamento do TOC sugerem a possível ação efetiva da psilocibina, e a partir de pesquisas relacionadas a outros transtornos, foram ampliados os estudos correspondentes sobre o potencial terapêutico da substância para o tratamento do TOC.…”
Section: Introductionunclassified